Handbook of Digital 3D Reconstruction of Historical Architecture - Münster, Sander; Apollonio, Fabrizio Ivan; Bluemel, Ina; Fallavollita, Federico; Foschi, Riccardo; Grellert, Marc; Ioannides, Marinos; Jahn, Peter Heinrich; Kurdiovsky, Richard; Kuroczyński, Piotr; Lutteroth, Jan-Eric; Messemer, Heike; et al. (Synthesis Lectures on Engineers, Technology, & Society, 2024)
This open access book is a handbook for students, experts and interested parties who want to learn more about digital 3D reconstruction of historical architecture. The book provides answers to the core questions of the subject: What is a digital 3D model or a digital 3D reconstruction? How are they created and what are they used for? Practical instructions, condensed knowledge, explanations of technical terms and references to example projects, literature and further references provide information of varying density and thus enable an individual introduction to the subject. The book combines extensive knowledge on the topic of "digital 3D reconstruction of historical architecture" and provides practical instructions for independent implementation. Up to now, there has been no cross-disciplinary vocabulary for technical terms in this field, so this publication makes a start. The book is aimed at students, experts in the field and the interested public and offers various possibilities for the different target groups to delve deeply into the subject. The book was created within the research network "Digital 3D Reconstruction as Tools for Research in Architectural History," which was funded by the German Research Foundation (DFG) from 2018 to 2023. The authors combined their expertise in the fields of art and architectural history, architecture, university teaching and media informatics.